ANALISIS MANAJEMEN KOMUNIKASI PADA PELAYANAN PERAWATAN PENYAKIT KUSTA TERHADAP PROSES PENYEMBUHAN PASIEN DI UNIT REHABILITASI KUSTA DONOROJO - Silavati, Yuni Adhita; Arso, Septo Pawelas; Kusumastuti, Wulan (Jurnal Kesehatan Masyarakat (Undip), 2020)
Rehatta Kelet Regional General Hospital, located in Jepara Regency deals with leprosy service only. Leprosy is an infectious disease caused by Mycobacterium Leprae which attacks the peripheral nerves and other body tissues. The preliminary study showed the leprosy patients' number hospitalized in the Leprosy Rehabilitation Unit (LRU) every year decreased the visitors' number from the 2017-2019 trend of 563 patients, 448 patients, and from January-October 2019 as many as 274 patients. The decreasing number of inpatient visits is not proportional to the increase in leprosy cases in Central Java because there are still many people and health workers in the Leprophobia Rehabilitation Unit (negative leprosy) and negative stigma, discrimination against people affected by leprosy and reporting from the district hospital and FKTP are late reporting and not fully affordable so that it could slow the healing process from leprosy. This research uses quantitative methods and a cross-sectional approach with 64 inpatients as samples. The results showed there was a relationship between communication management and the motivation of inpatient healing in the LRU, namely the aspect of information communication with a p-value of 0,000 and a correlation of 0.466, a clinical recording aspect with a p-value of 0.003 and a correlation of 0.371, an aspect of recording administration with a p-value of 0.012 and correlation of 0.313. It is recommended to the LRU to optimize and improve services in terms of officers and nurses also coordinating both with patients and their families to provide positive social support to support patient recovery.